Cu + 4 HNO3 → Cu(NO3)2 + 2 NO2 + 2 H2O
3 Cu + 2 HNO3 → 3 CuO + 2 NO + H2O ΔHo1 = -223 kJ
3CuO + 6HNO3 → 3Cu(NO3)2 + 3H2O 3* ΔHo2 = -276 kJ
4HNO3 + 2NO → 6 NO2 + 2H2O 2* ΔHo3 = 142 kJ
-----------------------------------------------------------------
3 Cu + 2 HNO3 + 3CuO + 6HNO3 + 4 HNO3 + 2NO
→ 3 CuO + 2 NO + H2O + 3Cu(NO3)2 + 3H2O + 6 NO2 + 2H2O
po skróceniu
3 Cu + 12 HNO3 → 3Cu(NO3)2 + 6 NO2 + 6H2O
ΔHor = ΔHo1 + 3* ΔHo2 + 2* ΔHo3
po skróceniu współczynników w równaniu reakcji /dzielimy przez 3/
Cu + 4 HNO3 → Cu(NO3)2 + 2 NO2 + 2H2O
ΔHor = 1/3 * (ΔHo1 + 3* ΔHo2 + 2* ΔHo3)
ΔHor = (-223 kJ +(-276 kJ) + 142 ) / 3 = - 119 kJ